Innovation and Integrated Structures of the Innovations in Modern Russia - Chuev, Ivan N.; Panchenko, Tatiana M.; Novikov, Vladimir S.; Konnova, Olga A.; Iraeva, Nadezhda G.; Karabulatova, Irina S. (International Review of Management and Marketing, 2016)
Integration processes contribute to the unification of educational, scientific and innovative capabilities of the leading educational centers in Russia. Formed a large market of educational services, increasing the scale of research and innovation work. Note that due to the association of universities, as well as through the effective use of various resources of universities combined probabilistic resulting indicators of the quality of educational services and innovations. Areas of high school with educational institutions at all levels requires a vertical type of links, it will give the opportunity to receive advanced education and research innovation of the corporation. On the scale of the region's integration institutions and bodies of vocational education determines the need to consolidate efforts for the employment of graduates, professional development and retraining, etc. The process of combining, merging dictate the need for a radical transformation of the education system to meet the requirements of the emerging knowledge economy, bringing adaptability and flexibility to adequately respond to current and future needs of socio-economic development of Russia and the world. Keywords: knowledge-based economy, regional economics, economics of education JEL Classifications: A2; D8; P25